Isolated Subtalar Repositional Arthrodesis Compared with Triple Arthrodesis for the Treatment of Progressive Collapsing Foot Deformity - Sunghoo Kim MD; HoSeong Lee MD, PhD (Foot & Ankle Orthopaedics)
Category: Hindfoot; Midfoot/Forefoot Introduction/Purpose: The optimal extent of arthrodesis for severe and rigid progressive collapsing foot deformity is controversial. Traditionally, triple arthrodesis has been recommended; however, good results have been reported using subtalar arthrodesis only. We compared the results of triple arthrodesis and isolated subtalar repositional arthrodesis. Methods: A total of 22 symptomatic feet were evaluated retrospectively. Isolated subtalar repositional arthrodesis was performed in 13 cases (the subtalar group) and double or triple arthrodesis in 9 cases (the triple group). Various radiographic variables for assessing flatfoot and osteoarthritic changes in ankle and tarsal joints were measured and compared between the 2 groups at 3 time points: preoperatively, 3 months postoperatively, and 4 years postoperatively. Additionally, we analyzed various factors that affect postoperative valgus talar tilt in the ankle joint, which has been associated with poor prognosis. Results: There were no differences in preoperative demographic data and the severity of the disease between the 2 groups; both groups showed improvement in radiographic parameters postoperatively compared with preoperative results. With the numbers available, no significant differences could be detected in postoperative radiographic measurements between the 2 groups. Of all the variables analyzed, postoperative hindfoot alignment angle was associated with postoperative talar tilt development. Additionally, postoperative talar tilt was observed more in triple group than in subtalar group. Conclusion: Isolated subtalar repositional arthrodesis is an effective and sustainable method of correcting advanced PCFD, with comparable outcomes to triple or double arthrodesis. In addition, patients with residual hindfoot valgus deformity are at risk of developing valgus talar tilt and therefore care should be taken to correct this deformity as completely as possible.